Excellent Nonlinear Optical M[M4Cl][Ga11S20] (M = A/Ba, A = K, Rb) Achieved by Unusual Cationic Substitution Strategy - Lou, Xiao‐Yu; Jiang, Xiao‐Ming; Liu, Bin‐Wen; Guo, Guo‐Cong (Small (Weinheim an der Bergstrasse, Germany), 2024)
The typical chalcopyrite AgGaQ2 (Q = S, Se) are commercial infrared (IR) second‐order nonlinear optical (NLO) materials; however, they suffer from unexpected laser‐induced damage thresholds (LIDTs) primairy due to their narrow band gaps. Herein, what sets this apart from previously reported chemical substitutions is the utilization of an unusual cationic substitution strategy, represented by [[SZn4]S12 + [S4Zn13]S24 + 11ZnS4 ⇒ MS12+ [M4Cl]S24 + 11GaS4], in which the covalent SxZny units in the diamond‐like sphalerite ZnS are synergistically replaced by cationic MxCly units, resulting in two novel salt‐inclusion sulfides, M[M4Cl][Ga11S20] (M = A/Ba, A = K, 1; Rb, 2). As expected, the introduction of mixed cations in the GaS4 anionic frameworks of 1 and 2 leads to wide band gaps (3.04 and 3.01 eV), which exceeds the value of AgGaS2, facilitating the improvement of high LIDTs (9.4 and 10.3 × AgGaS2@1.06 µm, respectively). Furthermore, compounds 1 and 2 exhibit moderate second‐harmonic generation intensities (0.84 and 0.78 × AgGaS2@2.9 µm, respectively), mainly originating from the orderly packing tetrahedral GaS4 units. Importantly, this study demonstrates the successful application of the cationic substitution strategy based on diamond‐like structures to provide a feasible chemical design insight for constructing high‐performance NLO materials. What sets this apart from previously reported chemical substitutions is the utilization of an unusual cationic substitution strategy, offers two excellent infrared nonlinear optical materials, which provides a feasible chemical design insight for constructing high‐performance nonlinear optical materials.